Reducing Sway of Gantry Crane Load - Nurfariza Binti Mohd Zuki, Nurfariza (2008)
Cranes are widely used for transportation of heavy material in factories, warehouse, shipping yards, building construction and nuclear facilities. This project is focused on gantry crane. There are several factors that will contribute to the crane swinging such as wind, crane design and operations. Hence, the objective of this project is to reduce and minimize the sway in order to reduce the operational time and cost.